Validity of the Human Respiratory System Booklets as Learning Suplement for Student Class VIII Junior High School - Ismi Azzahra Harahap; Helendra Helendra; Siska Alicia Farma; Syamsurizal Syamsurizal (Bioeducation Journal, 2020)
The education system in curriculum 2013 is emphasizing the active participation of students in learning by making students as subjects of learning. The application of the role of students as learning subjects can be maximized by the use of instructional media. Learning media commonly used in schools are students' books and student worksheets. The analysis that has been carried out reveals that the student book and the Student Worksheet have a weakness that is the appearance that does not attract students' interest and is not accompanied by relevant illustrations. This weakness was later made a reference to develop a respiratory system booklet in humans as a supplement to natural science learning for students of grade VIII junior high school. This research is a research development using the Plomp method. The research phase consisted of the preliminary research, development and prototypingt phase, and assessment phase. Data analysis uses quantitative and qualitative analysis. The booklet is validated by two validators. The booklet assessment stage is done by evaluating one using three students with different academic abilities. The results are obtaining booklets with a validation value of 89.56%. This study uses a self-evaluation questionnaire, expert reviews, and one-on-one evaluation. The conclusion obtained is that the booklet has very valid criteria and is very suitable for use as a learning supplement.